International Quit and Win 1996: comparative evaluation study in China and Finland. Issue 3 (1st September 2000) - Sun, Su; Korhonen, Tellervo; Uutela, Antti; Korhonen, Heikki J; Puska, Pekka; Jun, Yan; Chonghua, Yao; Zeyu, Guo; Yonghao, Wu; Wenqing, Xu
Abstract : OBJECTIVES: To compare background and process variables, as well as follow up status, of the participants in the International Quit and Win '96 contests of China and Finland, and analyse factors contributing to sustained maintenance. DESIGN: A standardised 12 month follow up was conducted in both countries with random samples of participants. The sample sizes were 3119 in China and 1448 in Finland, with response rates of 91.2% and 65.2%, respectively. INTERVENTIONS: The International Quit and Win '96 contest was the second coordinated, multinational smoking cessation campaign targeted at adult daily smokers. Altogether 25 countries participated, including China with 15 000 and Finland with 6000 smokers registered. MAIN OUTCOME MEASURES: Conservative (considering all non-respondents relapsed) and non-conservative (based on respondents only) estimates were calculated for one month abstinence, 12 month continuous abstinence, and point abstinence at the time point of follow up. RESULTS: Great differences were found in the background and process variables, as well as in the outcome measures. At one year follow up, the conservative continuous abstinence rates show that the Chinese participants maintained their abstinence better (38%) compared to the Finnish ones (12%). In China women reached higher abstinence rate (50%) than men (36%), whereas in Finland men achieved a better result (14%) than women (9%). CONCLUSIONS: The Quit and Win contest is a mass smoking cessation method feasible in countries showing great variance in smoking habits and rates. However, in countries with different stages of anti-smoking development, such as China and Finland, different practical implementation strategies may be needed.